(untitled) - Easton , Thomas A. (Boston, 2009)
Most fields of academic study evolve over time. Some evolve in turmoil, for they deal in issues of political, social, and economic concern. That is, they involve controversy.
Keywords: Energy conservation,Power resources,Tiết kiệm năng lượng,Nguồn năng lượng; Environmental aspects; United States,United States,Hoa Kỳ,Hoa Kỳ